Prescription Patterns of Antibiotics in Five Dermatologic Outpatient Clinics: A Cross Sectional Study from Yemen - Bahelah, Salwa Omer; Mohammed Abdo, Gamila (Journal of Pharmacy Practice and Community Medicine)
Background: Antibiotics represent one of the most commonly used medicines in dermatology. The objective of the present study is to assess the prescription patterns of antibiotics by dermatologists. Methods: A cross-sectional study was conducted in five dermatologic outpatient clinics in Aden Governorate, Yemen. Data were gathered using interviewer-administered questionnaire during the period January to October, 2014. The questionnaire was developed by the authors according to the objectives of the study, it includes patients-related (e.g., age, sex) and drug-related data (e.g., name of the drug, dosage, duration, route of administration and therapeutic efficacy). Data were analyzed by SPSS version 15. Results: During the study period, 320 patients were recruited in which 57.2% were females. The majority of female patients (69.4%) were in the age group 11-20 years while most male patients (60%) were in the age group 1-10 years. Most patients (28.4%) were diagnosed with eczema and dermatitis, followed by acne (22.5%). Macrolides (33.2%) were mostly prescribed followed by Penicillin (24.7%). One week duration of prescription of antibiotics for most cases (78.4%). Majority of cases (95.8%) improved clinically with the use of antibiotics that followed established therapeutic guidelines. Conclusion: Most cases had eczema and dermatitis, Macrolides were most commonly prescribed and one week duration prescribed for most cases. Most cases improved with guidelines followed.
Keywords: Antibiotics; Rational prescriptions; Skin infection; Yemen; Dermatology